Akbar birbal, pearls of truth - UNK (BPI INDIA New delhi, 2014)
The story "Fields of Pearls" from the Akbar Birbal: Pearls of Truth collection illustrates the perils of hypocrisy and the value of honesty. In this tale, Emperor Akbar seeks to test the integrity of his courtiers. Birbal, known for his wit, cleverly exposes their dishonesty, leading Akbar to reflect on the importance of truthfulness. The story underscores that those who claim to have never lied are often the most deceitful.